PERSEPSI MAHASISWA TERHADAP PENGGUNAAN MEDIA WHATSAAP DAN GOOGLE CLASROOM DALAM PEMBELAJARAN DARING MAHASISWA PENDIDIKAN BIOLOGI UNIVERSITAS COKROAMINOTO PALOPO - eva sohriati (Jurnal Biogenerasi, 2021)
One of the efforts to prevent the spread of Covid-19 in the educational environment, the Ministry of Education and Culture, responded with a "study from home" policy. The purpose of this study was to determine students' perceptions of the use of WhatsApp and Google Classroom media in online learning for Biology students at Cokroaminoto University, Palopo. With this appeal, the learning process for biology education at Cokroaminoto Palopo University is carried out from home by utilizing technology and internet media. This research was conducted using a descriptive survey research method. The sample in this study was 27 students as respondents consisting of 2 classes, namely grades 6A and 6B. The collection of lecturers' perception data is carried out through the provision of questionnaires (questionnaires), through a google form to lecturers who have carried out online learning. The results of the study indicate that the most widely controlled learning media and facilitate students in online learning is whatsaap media.